From spanning forests to edge subsets - Trinks, Martin (Ars mathematica contemporanea, 2014)
We give some insight into Tutte's definition of internally and externally active edges for spanning forests. Namely we prove, that every edge subset can be constructed from the edges of exactly one spanning forest by deleting a unique subset of the internally active edges and adding a unique subset of the externally active edges.
Keywords: edge subsets; spanning forests; teorija grafov; Tutte polynomial